Anxiety-Related Silence in Speaking among Indonesian EFL Junior High School Students - Adi Budi Perkasa; Dian Savitri; Yogyantoro Yogyantoro (Universitas Ahmad Dahlan, 2022)
As a foreign language, learning English in the classroom often experiences problems. One form of teacher difficulties experienced in the classroom is the silent phase of a student when the learning process takes place. This does not only happen when the teacher explains the material, but also when students are asked to answer questions or practice talking to their friends. This article will discuss the silence that occurs in students when they are asked to speak in English. The method used is qualitative by using data triangulation to strengthen the research results. The subjects of this study were 8th grade students from 3 different provincial schools, they are SMPN 1 Sukahening, Tasikmalaya, West Java; SMPN 2 Tayu, Pati, Central Java and SMPN 4 Muara Teweh, Central Kalimantan. Taking this subject is used to see whether the silence experienced by students in each place has the same meaning or not. The results showed that effect of silence in the classroom on English learners triggering negative thoughts, feelings and emotions. The silence experienced by students was caused by several factors, such as low English mastery, lack of self-confidence and lack of preparation.